Machine learning estimation of aerosol size distributions from meteorological data in the Western Himalayas - Alok Sagar Gautam; Aman Deep Vishwkarma; Karan Singh; Sanjeev Kumar; Yasti Panchbhaiya; Sneha Gautam; Chang-Hoi Ho; Yong-Sang Choi (Theoretical and Applied Climatology, 2026)

Depositional history of a wave-dominated, storm-infested argillaceous late Miocene–Pliocene shelf from the Boka Bil Formation, Surma Group, Mizoram, India - Ujjwal Kr Singh; Partha Pratim Chakraborty; Lalramengi Fanai; Lalremruata; Alok Deep; Paul Lalnuntluanga (Journal of Earth System Science, 2026)

Comprehensive Assessment of Air Quality During Diwali Celebrations in Himalayan Foothill Cities - Ankur Kansal; Parag Madhukar Dhakate; Amar Deep; Alok Sagar Gautam; Sneha Gautam (Aerosol Science and Engineering, 2026)

Study of Aerosols Optical Depth and Ångström Exponent Over IGP: A Case Study - Pushpendra Singh Soni; Vikram Singh; Alok Sagar Gautam; Amar Deep; Rolly Singh; Alka Gautam; Sneha Gautam; Surendra Pratap Singh (Aerosol Science and Engineering, 2026)

Geochemistry and U–Pb Geochronology of Volcaniclastic Rocks From the NW Lesser Himalayan Sequence: Implications for Arc‐Related Tectonic Setting at Northern Proto‐Indian Continental Margin During the Neoproterozoic - Subhojit Saha; Kaushik Das; Shivani S. Choudhari; Abhishek Kumar Pandey; Shruti Ranjan Mishra; Sumit Kumar Ghosh; Alok Deep; Partha Pratim Chakraborty (Island Arc, 2026)
The protracted tectonic history concerning the northern edge of the pre‐Himalayan proto‐Indian plate margin during the Neoproterozoic time has been a long‐standing subject of debate, with various hypotheses enduring over several decades. Although a continental rift to passive margin setting has been proposed for the deposition of Neoproterozoic rocks of the Outer Lesser Himalayan Sequence (OLHS), the similarity in detrital zircon age peaks and Nd isotope values of OLHS rocks with those of the Higher Himalayan Crystalline Sequence (HHCS) led to the proposition of an arc‐related setting. So far, there is no such report of Neoproterozoic arc‐related magmatism from the Lesser Himalayan Sequence. In the present study, an interbedded volcaniclastic horizon has been identified from the basal stratigraphic level of the Nagthat Formation, OLHS. Geochemistry and U–Pb zircon geochronology are used to understand the provenance and tectonic setting of the Nagthat volcaniclastic rock. The angularity of the framework minerals, moderate degree of weathering (avg. Chemical Index of Alteration value 62), and immature nature (Index of Compositional Variability 1–1.1) suggest that a contemporaneous volcanic province was probably the main source. Whole rock geochemical analysis shows high Th/Sc (1.67–3.40, avg. 2.71), La/Sc (4.74–8.21, avg. 7.14), and low Cr/Th ratios (1.78–5.45, avg. 3.02). It supports that the volcaniclastic was supplied from an acid to intermediate source rocks, such as rhyolite and dacite/andesite. U–Pb detrital zircon analysis yielded a major age peak around 775 Ma. However, comparison of the U–Pb zircon age data with published datasets from the Lower (Chandpur Formation) and upper (Nagthat Formation) stratigraphic horizons suggests a timing of volcanism between 800 and 700 Ma. Geochronological and geochemical characteristics of the volcaniclastic rock suggest a signature transitional from passive to active continental margin setting, indicating that at least subduction was ongoing during the Tonian (800–700 Ma) at the northern proto‐Indian plate margin.

Continental (fluvial) to marine (tidal) transition in Paleoproterozoic Rautgara Formation, Inner Lesser Himalaya (ILH), Garhwal Himalaya - Alok Deep; Partha Pratim Chakraborty (Journal of Earth System Science, 2025)

Identification of EhTIF-IA: The putative E. histolytica orthologue of the human ribosomal RNA transcription initiation factor-IA - Ankita Srivastava; Alok Bhattacharya; Sudha Bhattacharya; Gagan Deep Jhingan (Journal of Biosciences, 2016)